Напряжения и деформации железобетонных мостовых конструкций - Матаров Иван Александрович (Транспорт, 1973)
Экземпляры: КХ (20240607) / Инвентарный номер: 569983 / Сис.шифр: 690.2 / Авт.знак: М 33 / ГРНТИ: 67 / ББК: 38